On reconstruction of strain fields from tomographic data. (26th June 2015) - Palamodov, V
Abstract: A method of reconstruction of a strain tensor ϵ in a solid body was described that uses non-redundant data of the axial (longitudinal) and of the traceless normal ray integrals.